KUALITAS PELAYANAN PUBLIK BERBASIS DIGITAL TERHADAP TINGKAT KEPUASAN MASYARAKAT DI DESA BULO - Saputri, Annisa; Lukman; Uceng, Andi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The aim of this research is to determine the quality of digital-based public services and the level of community satisfaction in Bulo Bulo village as well as the influence of digital-based service quality on the level of community satisfaction.The population in this study was 182 people and the sample was 64 people. The sampling technique is nonprobability sampling. This type of research is Quantitative Associative. The data collection techniques used in this research were observation, questionnaires and literature study. The data analysis techniques used are measurement scale instruments, reliability testing and simple linear regression analysis using SPSS 16.0 and a Likert Scale. The results of this research from the results of the questionnaire obtained a recapitulation of the service quality variable of 67% in the "Good" category. The recapitulation of the community satisfaction variable was 64% in the "Good" category. The influence between Service Quality and community satisfaction in Bulo Village is categorized as "Influential/Significant", from the ANOVA test the F count obtained is 2127.592 with a significance level of 0.000. This shows that the influence of the independent variables as a whole has a significant effect, and the probability is far above 0.05, overall partial t count (46,126) > t table (1,671) meaning that the quality of digital-based public services has a significant/influence on the level of community satisfaction in Bulo Village of 97.2%.